Takhrij and Syarah Hadith of Chemistry: Maintaining Environmental Cleanliness by Reducing Plastic Waste - Finna Fitriyani Soleha; Diah Kusumawardani; Dede Suhendar; Husnul Qodim; Yulianti Yulianti (Gunung Djati Conference Series, 2021)
The purpose of this research is to discuss the hadith of the Prophet SAW. about cleanliness. This research method is qualitative through the approach of takhrij and sharah hadith with chemical analysis. The result and discussion of this research are to maintain environmental cleanliness by reducing plastic waste so that it can reduce the occurrence of environmental pollution. This research concludes that keeping the environment clean is highly recommended by the Prophet SAW. based on takhrij and sharah hadith. This study recommends developing efforts to maintain environmental cleanliness by reducing plastic waste.